Analysis of Motivation and Learning Difficulties in Mandarin Among Non-Chinese Indonesian Students at the University in Makassar - Azizah, Mir'ah (Civiliza Publishing, Indonesia., 2025)
The increasing global influence of China and its economic rise have made Mandarin Chinese a valuable skill for international communication and job opportunities, especially in countries like Indonesia that maintain close economic ties with China. The research aims to understand the dominant types of motivation and to identify common obstacles students encounter in acquiring the language. A mixed-method approach was used, combining quantitative descriptive methods through questionnaires distributed to 69 first- and second-year students, and qualitative methods through interviews with 10 students. The findings reveal that most students are instrumentally motivated, driven by the desire for better employment prospects and educational advancement, rather than integrative factors such as cultural interest or native-like fluency. Major learning difficulties include pronunciation (particularly tones and retroflex consonants), grammar, and the memorization and writing of Chinese characters (hanzi), largely due to interference from the Indonesian language and limited exposure to Mandarin in their environment. Despite these challenges, students exhibit a generally positive learning attitude, especially in classroom participation. This study concludes that greater support in pronunciation, grammar instruction, and character acquisition is necessary, and suggests that future research explore broader contexts and more advanced student groups.